On the Controversy of Classicism - Edwin Chan (Oz, 1987)
Collaborator in design: Carroll Stockard The subject of classicism has been the focus of numerous architectural debates in the last few years. While advocates proclaim its rational tectonic discourse an alternative to the eclectic practice of post-modernism, its antagonists reject its dogmatic principles as contradictory to the progress of modernity. Earlier this year, the same controversy exploded in unprecedented magnitude during the jury of an international design competition when the four noted judges/architects tried to select a first-place winner. The following is an excerpt from the heated debate.